Modelo de negocio para la creación de un operador turístico en el municipio de Pereira (2023)
This degree work is a structuring tool that allows to have a solid base for the opening of a travel agency, which includes the legal, labor and sustainability requirements (environmental, social and economic) for the operation of a tour operator. It was carried out through a methodology called: Business Model Canvas, where the components of: value proposition, market segment, customer relationship, distribution channels, key activities, key resources, key associates and cost structure.